Mediating role of grip strength between depression symptoms and cognitive function: A cross-sectional study among older adults with diabetes in rural areas. - Xueyan Liu; Fangyun Luan; Lijuan Xiao; Yingjuan Cao (PLoS ONE)
Older adults with diabetes are at an increased risk for both depression and cognitive decline. Depression symptoms have been linked to poorer cognitive function. Grip strength, an indicator of physical function, may play a role in this relationship. However, the specific mechanisms connecting depression, grip strength, and cognitive function in older adults with T2DM in rural areas are not fully understood. The objective of this study was to analyze the mediating role of grip strength in the relationship between depression symptoms and cognitive function. This Cross-sectional study was conducted from April to July 2023 in rural areas of China. To compare characteristics between male and female participants, one-way ANOVA and Chi-squared tests were used. Multivariate linear regression analysis was performed to examine the relationships between depression symptoms, grip strength, and cognitive function, adjusting for potential confounders. Bootstrap analysis, with 5000 resamples, was employed to assess the mediating role of grip strength in the relationship between depression symptoms and cognitive function. The study included 898 older adults with T2DM, with an average age of 69.73 years. Depression symptoms were found to be negatively associated with cognitive function. Grip strength was identified as a mediator in this relationship. Bootstrap analysis confirmed the partial mediating effect of grip strength, explaining 9% of the total effect of depression symptoms on cognitive function. These findings contribute to a better understanding of the underlying mechanisms between depression symptoms and cognitive function, elucidating the mediating role of grip strength in this association.